2017
DOI: 10.1177/0961203317731533
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance detects silent heart disease missed by echocardiography in systemic lupus erythematosus

Abstract: Background Accurate diagnosis of cardiovascular involvement in systemic lupus erythematosus (SLE) remains challenging, due to limitations of echocardiography. We hypothesized that cardiovascular magnetic resonance can detect cardiac lesions missed by echocardiography in SLE patients with atypical symptoms. Aim To use cardiovascular magnetic resonance in SLE patients with atypical symptoms and investigate the possibility of silent heart disease, missed by echocardiography. Patients/methods From 2005 to 2015, 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…We have previously reported that occult CMR lesions, including myocardial odema, myocarditis, diffuse subendocardial fibrosis and myocardial infarction are not unusual in treatment naïve ARD patients, and may be reversible after appropriate treatment [46]. Similarly, cardiac lesions, missed by echocardiography, were detected by CMR in SLE patients in another study by our group [47]. The CMR findings in the current ARD cohort are thus in agreement with previous literature by our group and others regarding the spectrum of CMR lesions in ARDs [23,[31][32][33].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We have previously reported that occult CMR lesions, including myocardial odema, myocarditis, diffuse subendocardial fibrosis and myocardial infarction are not unusual in treatment naïve ARD patients, and may be reversible after appropriate treatment [46]. Similarly, cardiac lesions, missed by echocardiography, were detected by CMR in SLE patients in another study by our group [47]. The CMR findings in the current ARD cohort are thus in agreement with previous literature by our group and others regarding the spectrum of CMR lesions in ARDs [23,[31][32][33].…”
Section: Discussionmentioning
confidence: 60%
“…As such, this demonstrates the need for a combined brain and heart MRI examination in ARD patients with cardiac symptoms, seeing as disease progression may evolve differently in the two organs. Notably, our group has previously reported that CMR findings are independent of C-reactive protein levels in ARD patients [47,51,52], often rendering biomarker-based pre-selection of patients for CMR examinations problematic. This would explain the current findings and suggests that such inflammatory biomarkers might have greater utility in evaluating brain involvement than cardiac involvement, although this needs to be corroborated by future independent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the patient's condition, the use of CMR can be restricted. Cardiac involvement in the absence of typical cardiac symptoms detected via CMR can be missed on transthoracic echocardiography (TTE); therefore, a new routine indicator is required [10].…”
Section: Introductionmentioning
confidence: 99%
“…У переважній більшості випад-ків СЧВ виявляють зміни систоло-діастолічної функції лівого шлуночка [4,5], а у деяких пацієн-тів також дисфункції правого шлуночка і перед-сердя [6, 7]. Добре відомі спостереження рапто-вої смерті хворих на СЧВ внаслідок гострої серце-вої недостатності [8].Ознаки ураження серця при СЧВ у вигляді міо кардиту, коронариту, інфаркту міокарда, пору-шень кардіального ритму (процесів збудливості й електричної провідності) вельми неспецифічні, часто-густо складні для діагностики, а різні ланки їх патогенезу вимагають уточнення [9][10][11]. Особ-ливої значущості набуває вовчаковий ендокар-дит Лібмана-Сакса [12, 13] з формуванням кла-панних вад серця [14].…”
unclassified
“…Ознаки ураження серця при СЧВ у вигляді міо кардиту, коронариту, інфаркту міокарда, пору-шень кардіального ритму (процесів збудливості й електричної провідності) вельми неспецифічні, часто-густо складні для діагностики, а різні ланки їх патогенезу вимагають уточнення [9][10][11]. Особ-ливої значущості набуває вовчаковий ендокар-дит Лібмана-Сакса [12, 13] з формуванням кла-панних вад серця [14].…”
unclassified